2002
DOI: 10.1021/jf011718g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Natto, A Kind of Fermented Soybeans, on LDL Oxidation in Vitro

Abstract: The oxygen radical scavenging activity of natto (fermented soybeans) and its inhibitory effect on the oxidation of rat plasma low-density lipoprotein (LDL) in vitro were investigated to evaluate the usefulness of the antioxidant properties of natto, which has been shown to have antioxidant activity. Natto was separated into three water-soluble fractions: high-molecular-weight viscous substance (HMWVS; Mw > 100 000), low-molecular-weight viscous substance (LMWVS; Mw < 100 000), and soybean water extract (SWE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…When a protease (Prozyme 6) was added after 5 h fermentation, much lower IC50-value (0.66 mg/ml) was obtained. Natto has shown to have radical scavenging activity and inhibitory effect on the oxidation of rat plasma LDL in vitro [79]. The aqueous extracts of Douchi showed radical scavenging activities and chelating ability of ferrous ions.…”
Section: Production Of Peptidesmentioning
confidence: 97%
“…When a protease (Prozyme 6) was added after 5 h fermentation, much lower IC50-value (0.66 mg/ml) was obtained. Natto has shown to have radical scavenging activity and inhibitory effect on the oxidation of rat plasma LDL in vitro [79]. The aqueous extracts of Douchi showed radical scavenging activities and chelating ability of ferrous ions.…”
Section: Production Of Peptidesmentioning
confidence: 97%
“…All three CKJ exhibited an 80% scavenging of •OH at the 100 μg/mL concentration and for ONOO -removal at the 250 μg/mL concentration, revealing a very powerful antioxidant activity. Low-molecular-weight viscous substance (<100,000) of natto showed a stronger •OH scavenging activity than that for O 2 -, determined by ESR at 10 mg/mL concentration (19). From these data we could conclude that fermented soybean products by Bacillus species have a great ROS scavenging activity, especially for •OH.…”
Section: Discussionmentioning
confidence: 70%
“…One important finding observed in our study is that CKJ possesses a great potential for scavenging •OH and ONOO -. Numerous researchers have cited that fermented soybean products such as natto (19), miso (20), dou-chi (21) doenjang (9), CKJ (9,22), and Lactobacillusfermented soybean products (23) possess antioxidant activities. The antioxidant activity of fermented soybean product originally comes from the phenols and flavonoids present in the soybean (24), the concentrations of which are increased after fermentation (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys have demonstrated that isoflavones in soybeans act as antioxidants (11,12), improve lipoprotein profiles (13), delay osteoporosis in the elderly (14,23) and may protect against cancer (15). These effects are independent of vitamin K action as a cofactor of ␥-glutamyl carboxylase.…”
Section: Discussionmentioning
confidence: 99%